The returns to language skills in the US labor market - Ingo Eduard Isphording; Mathias Sinning (Institute for the Study of Labor (IZA), 2012)
This paper uses data from the 2010 American Community Survey (ACS) to study the returns to language skills of child and adult migrants in the US labor market. We employ an instrumental variable strategy, which exploits differences in language acquisition profiles between immigrants from English- and non-English-speaking countries of origin, to address problems related to endogeneity and measurement error. We find significantly positive returns to language skills and demonstrate that education is an important channel through which language skills affect wages of child migrants. Although the returns of adult migrants do not depend on education, we find that child and adult migrants exhibit similar returns to language skills.
Keywords: F22; J24; J31; 330; international migration; language skills; labor productivity; Migranten; Mehrsprachigkeit; Bildungsertrag; Arbeitsproduktivität; USA